PROBLEMS OF TRADE-ECONOMIC COOPERATION OF THE RUSSIAN FEDERATION AND THE KYRGYZ REPUBLIC WITHIN THE FRAMEWORK OF THE EAEU - A. Ormonova (Вестник университета)
This article is devoted to a brief analysis of trade and economic cooperation between the Federation and the Kyrgyz Republic within the framework of the Eurasian Economic Area. The article examines the problems and topical issues of the accession of the Kyrgyz Republic to the Eurasian Economic Union and the Customs Union, where serious socioeconomic, political and cultural transformations began, as well as the influence of Russia's main strategic partner on the all-round development of The republic.